Desperation in Death - Robb, J. D. 1950- (New York : St. Martin's Press, 2022)
"The #1 New York Times bestselling author presents a gripping new thriller that pits homicide detective Eve Dallas against a conspiracy of exploitation and evil..."--
Keywords: Detective and mystery fiction; Novels